Control system design - Goodwin, Graham C. (Graham Clifford), 1945-; Graebe, Stefan F., ....-; Salgado, Mario E., ....- (New Jersey : Prentice Hall, 2001)
Much has been written about the need to revitalize control education. This book addresses the problem by providing a refreshing new approach to teaching control system design. The book strongly emphasizes real-world design, making it appropriate for the first-time learner as well as for engineers in industry as a technology refresher. The book has been used by the authors for both undergraduate and graduate courses at several universities. The authors' experience is split evenly between academia and industry, which is reflected in the contents of the book. It is divided into 8 parts covering essential aspects in control, ranging from signals and systems (Bode diagrams, root locus, etc.), to SISO control (including PID and fundamental design tradeoffs), and MIMO systems (including constraints, MPC, decoupling, etc.). A key aspect of the book is the frequent use of real world design examples drawn directly from the authors' industrial experience. These are represented by over 15 substantial case studies ranging from distillation columns to satellite tracking. The book is also liberally supported by modern teaching aids available on both an accompanying CD-ROM and Companion Website. Resources to be found there include MATLAB® routines for all examples; extensive PowerPoint lecture notes based on the book; and a totally unique Java Applet-driven 'virtual laboratory' that allows readers to interact with the real-world case studies.For both undergraduate and graduate courses in Control System Design. Using a 'how to do it' approach with a strong emphasis on real-world design, this text provides comprehensive, single-source coverage of the full spectrum of control system design. Each of the text's 8 parts covers an area in control-ranging from signals and systems (Bode Diagrams, Root Locus, etc.), to SISO control (including PID and Fundamental Design Trade-Offs) and MIMO systems (including Constraints, MPC, Decoupling, etc.).
Includes bibliographical references and index
Keywords: Control; Engineering Design